The Influence of Current Ratio, Net Profit Margin, Debt to Equity Ratio on Stock Prices of Cigarette Companies Listed on the Indonesia Stock Exchange from 2018-2021 - Novita S.G Siahaan; Puput Sanny Casanova Sidabalok; Christine Sitanggang; Perbawaty Angelica; Helman Helman; Fajrillah Fajrillah (Kusuma Negara Business School, 2023)
The aim of this research is to discern the correlation between the Current Ratio, Net Profit Margin, and Debt to Equity Ratio variables, and the stock price movement of tobacco companies that have operating licenses on the Indonesia Stock Exchange (IDX) during the period of 2018-2021. The most appropriate method for this research topic is multiple linear regression analysis. This study has successfully passed classical assumption tests, which include normality, multicollinearity, autocorrelation, and heteroskedasticity tests. The purposive sampling method was utilized for the selection of research samples. Out of the total population, only three companies met the criteria and were selected as samples for this study. Based on the research findings, it has been demonstrated that the Current Ratio has a positive and significant correlation with stock price movement when considered individually. Similarly, the Net Profit Margin also exhibits a positive and significant correlation with stock price movement. However, no positive correlation has been observed between the Debt to Equity Ratio and the Stock price. In addition to these findings, it has been observed that the Current Ratio, Net Profit Margin, and Debt to Equity Ratio simultaneously exhibit a positive and significant correlation with the closing prices of shares of tobacco companies. This suggests that these three variables need to be collectively taken into account when analyzing the factors that influence the stock price movement of tobacco companies listed on the IDX.